The Influence of Service Quality and Facilities of Community Health Centers on the Loyalty of Prolanis Patients Mediated by Patient Satisfaction at the Manis Jaya Community Health Center - Anggraini, Rini Dian (Journal of Management and Administration Provision, 2025)
This research is rooted in the challenges faced by the Manis Jaya Community Health Center in improving the quality of services and health facilities, particularly in the context of the increasing prevalence of non-communicable diseases (NCDs) in the community. Patient satisfaction is a key factor in creating loyalty, especially for participants in the Chronic Disease Management Program (PROLANIS). This study aims to explore the influence of service quality and facilities on PROLANIS patient loyalty, with patient satisfaction as a mediating variable. The method used in this research is a quantitative approach with a cross-sectional design, involving 101 respondents selected through purposive sampling techniques. The data obtained were analyzed using Structural Equation Modeling (SEM) and Partial Least Squares (PLS) to test the proposed hypotheses. The results of the study indicate that service quality has a positive and significant effect on patient satisfaction (t-statistic 4.350, p-value 0.000), and facilities also significantly contribute to patient satisfaction (t-statistic 3.719, p-value 0.000). Furthermore, patient satisfaction has been shown to positively influence PROLANIS patient loyalty (t-statistic 3.750, p-value 0.000). The conclusion of this study emphasizes that improving the quality of services and facilities at the Manis Jaya Community Health Center not only enhances patient satisfaction but also plays a crucial role in building patient loyalty towards the PROLANIS program. These findings are expected to serve as a reference for health service managers in formulating sustainable quality improvement strategies.